Long-term preservation of cardiac structure and function after adeno-associated virus serotype 9-mediated microdystrophin gene transfer in mdx mice - Schinkel, Stefanie; Bauer, Ralf; Bekeredjian, Raffi; Rutschow, Désirée; Katus, Hugo; Müller, Oliver J. (Human gene therapy, 2012)
Dystrophin plays an important role in muscle contraction, linking the intracellular cytoskeleton to the extracellular matrix. Mutations of the dystrophin gene leading to a complete loss of the protein cause Duchenne muscular dystrophy (DMD), frequently associated with severe cardiomyopathy. Early clinical trials in DMD using gene transfer to skeletal muscle are underway, but gene transfer to dystrophic cardiac muscle has not yet been tested in humans. The aim of this study was to develop an optimized protocol for cardiac gene therapy in the mouse model of dystrophin deficiency (mdx), using a cardiac promoter for expression of a microdystrophin (μDys) transgene packaged into an adeno-associated virus serotype 9 vector (AAV9). In this study adult mdx mice were intravenously injected with 1×1012 genomic particles of AAV9 vectors carrying a cDNA encoding μDys under the control of either a ubiquitously active cytomegalovirus (CMV) promoter or a cardiac-specific CMV-enhanced myosin light chain (MLC0.26) promoter. After 10 months, both AAV9 vectors led to sustained μDys expression in cardiac muscle, but the MLC promoter conferred about 4-fold higher protein levels. AAV9-CMV-MLC0.26-μDys resulted in significant protection of cardiac morphology and function as assessed by histopathology, echocardiography, and left ventricular catheterization. In conclusion, we established an AAV9-mediated gene transfer approach for efficient and specific long-term μDys expression in the hearts of mdx mice, resulting in a sustained therapeutic effect. Thus, this approach might be a basis for further translation into a treatment strategy for DMD-associated cardiomyopathy.
Gesehen am 08.05.2018